Brand Image Analysis Of Sales With Product Quality As Samsung Electronic Indonesia Intervening Variables - Hary Mulyadi (Sekolah Tinggi Agama Islam Kuningan, 2022)
In terms of business development, electronic products circulating in the Indonesian market also compete with each other for profit. This study discusses issues related to brand image, product quality that affect the sales of Samsung Elektronic Indonesia Company in Jakarta. The purpose of this study is to analyze the influence of brand image, product quality that affects sales of Samsung Elektronik Indonesia Company in Jakarta. This research is a survey research, interviews, questionnaires to collect all the primary data information needed in the study. Data were collected from 100 respondents and PLS-SEM was used as a measuring tool between research variables and path analysis. The results of this study indicate that the path value of the brand image coefficient is 0.620 for product quality, product quality is 0.797 for sales. Brand image of 0.022 to sales. Product quality as an intervening variable also has an effect on sales of 0.494. Implications and suggestions are described in this study.